The Paradox of Help Seeking in the Entropy Mastermind Game - Taylor, Nichola; Hofer, Matthias; Nelson, Jonathan D. (Frontiers in Education, 2020)
Research on Bayesian reasoning suggests that humans make good use of available information. Similarly, research on human information acquisition suggests that Optimal Experimental Design models predict human queries well. This perspective contrasts starkly with educational research on help seeking, which suggests that many students wait excessively long to ask for help, or even decline help when it is offered. We bring these two lines of work together, exploring when people seek help as a function of problem state in the Entropy Mastermind code breaking game. The Entropy Mastermind game is a probabilistic version of the classic code breaking game, involving inductive, deductive and scientific reasoning. Whether help in the form of a hint was available was manipulated within subjects. Results showed that participants tended to ask for help late in the game play, often when they already had all the necessary information needed to crack the code. These results pose a challenge for the Bayesian and Optimal Experimental Design frameworks and highlight the importance of considering whether other forms of help could be more effective.